Forecasting the Value of Natural Rubber Exports - เรียนสุทธิ์ , วรางคณา (Progress in Applied Science and Technology, 2019)
The objective of this study was to construct the appropriate forecasting model for the value of natural rubber exports. The data gathered from the website of the Office of Agricultural Economics from January 2011 to December 2018 of 96 values were used and divided into 2 sets. The first set had 84 values from January 2011 to December 2017 for constructing the forecasting models by Box-Jenkins method, Holt’s exponential smoothing method, damped trend exponential smoothing method, and combined forecasting method. The second set had 12 values from January to December 2018 for comparing the accuracy of the forecasts via the criterion of the lowest mean absolute percentage error. Research findings indicated that for all forecasting methods that had been studied, the most accurate method was combined forecasting method.